O ATELIÊ NA EDUCAÇÃO INFANTIL: UM ESTUDO COM GESTORAS E PROFESSORAS DO NÚCLEO INFANTIL LUIZINHO DE GRANDI SANTA MARIA, RS - Pagnossim, Deise Minuzzi (2023)
In this study, the objective was to understand the impacts of the organization and dynamization of the Workshops in Education for the pedagogical work of teachers and managers of a school in the Municipal Education Network of Santa Maria, RS. For that, the following specific objectives were determined: to map the master's dissertations of the Catalog of the Theses and Dissertations, having as a selection the works produced based on Reggio Emilia workshop; to describe how the organization and dynamics of the Workshops in Early Childhood Education at a school in the Municipal Education Network of Santa Maria take place; to analyze the teachers and managers’ perception on the practice of Workshops in a municipal school of Early Childhood Education in the municipality of Santa Maria, RS; to investigate the managers’ contribution for the development process of the Workshops with Early Childhood Education classes. The methodology used was a qualitative approach based on case study. The participants in this research were two managers who exercise the position of pedagogical coordination, the school principal and a teacher from each stage of Early Childhood Education, from baby nursery up to preschool, a total of four teachers and three managers. After the data collection, which was made from a questionnaire with managers and teachers, it was possible to identify that Reggio Emilia approach inspires the school in a study to adapt the Workshops practices into the local reality. It highlights the positive impact that enables reinterpretations of the pedagogical practice in Early Childhood Education. This way, it enhances children's learning and diversifies the pedagogical work proposed in the school community.